Investigation of novel SMF-capillary-NCF-SMF sensor for simultaneous measurement of NH3 concentration and temperature - Zhu, Feng; Zhao, Hengyang; Xu, Xiaoxiao; Deng, Chuanlu; Liu, Zetian (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
A dual parameter fiber optic sensor is proposed, which is based on a cascade single mode fiber (SMF)-capillary-no core fiber (NCF)-SMF (SCNS) structure. The sensor introduces a capillary to the conventional SMF-NCF-SMF (SNS) structure, which improves the excitation co-efficient of the higher order modes in the NCF. The optimized ZnO film thickness of the SCNS sensor is 100 nm by simulation, which can enhance the sensitivity of the sensor greatly. The experimental results show that the resonant wavelength has different sensitivities to NH3 concentration and temperature. The maximum NH3 concentration sensitivity is 35.52 pm/ppm, with a detection limit of 2.309 ppm, and the maximum temperature sensitivity is 25.85 pm/°C. Based on the different spectral responses, a cross-matrix is developed to enable the simultaneous measurement of temperature and NH3 concentration.
Optica Applicata, Vol. 55, 2025, nr 1, s. 63-76
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; cross-matrix calibration; temperature; NH3 concentration; dual parameter sensing; fiber optic sensor